2018
DOI: 10.1007/s11060-018-2968-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of dose escalation using intraoperative radiotherapy following resection of large brain metastases compared to post-operative stereotactic radiosurgery

Abstract: Critical organ dosimetry for IORT remains generally lower than that achieved with single fraction SRS following resection of large brain metastases. We recommend 30 Gy to surface as the preferred prescription, consistent with the dose recommendation for IORT in glioblastoma used in the ongoing INTRAGO-II phase-III trial. Early clinical outcomes appear promising for surgery and IORT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…After publication of the toxicity data of the INTRAGO phase1/2 study [25], we have increased dose stepwise and since 2016, all patients have been irradiated with 20 Gy. Other centers nowadays apply even higher doses [13,25,26]. However, with the reported outcome of our patients we do not see a necessity for further dose escalation currently.…”
Section: Discussionmentioning
confidence: 52%
“…After publication of the toxicity data of the INTRAGO phase1/2 study [25], we have increased dose stepwise and since 2016, all patients have been irradiated with 20 Gy. Other centers nowadays apply even higher doses [13,25,26]. However, with the reported outcome of our patients we do not see a necessity for further dose escalation currently.…”
Section: Discussionmentioning
confidence: 52%
“…Dosimetric comparisons have determined the feasibility of dose escalation with kilovoltage-IORT (kV-IORT), confirming a clear benefit in terms of healthy tissue sparing [ 10 ]. After these considerations, initial clinical experiences with kV-IORT have been reported during the last decade.…”
Section: Letter Bodymentioning
confidence: 99%
“…Conversely, larger cavities treated with intraoperative cesium-131 (Cs-131) implants have demonstrated excellent LC [17,19]. Previous trials with iodine-125 brachytherapy have also demonstrated very good LC in both large and small resected tumor cavities [37,38]. Interestingly, multidose SRS (9Gy x 3) has also shown good LC of 93% at one year for large (>3 cm) brain metastases [39], although this has not been commonly replicated.…”
Section: Reviewmentioning
confidence: 99%
“…Brachytherapy such as Cs-131 is also advantageous over SRS in cases of recurrent brain metastases in brains that have already been irradiated, as repeat irradiation greatly increases the risk of radiation necrosis [36]. This is because brachytherapy has the advantage of a steep dose fall-off outside of the immediate area of the resection cavity, leading to less irradiation of normal tissue [19,38]. Also, it has been hypothesized that immediate implantation of brachytherapy seeds may improve LC by counteracting the tumor-cell proliferation and dissemination caused by the surgical manipulation of the microenvironment during resection [38].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation